Palliative Care from the Beginning of Treatment for Advanced Pancreatic Cancer - Lazenby, James Mark; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Palliative care ought to be offered at the initiation of treatment for people who are diagnosed with pancreatic cancer, given the poor relative survival rate and the intractable symptom profile of those who have this life-limiting disease. In this article, we argue that palliative treatment of people with pancreatic cancer is not found in extending survival, but rather, in promoting quality of life. This argument is made by reviewing the literature on the state of palliative care in pancreatic cancer and by summarizing key studies presented at the "2010 ASCO Gastrointestinal Cancers Symposium" held in Orlando, FL, USA on January 22-24, 2010. The studies discussed here include: i) a study of a random sample of 564 patients with pancreatic cancer that found that the symptom cluster of fatigue and pain predicted survival (Abstract #265); ii) a retrospective study of 108 patients that identified anticoagulation therapy in those who developed portal vein thrombosis prolonged survival (Abstract #143); iii) a double-blind randomized control trial of 50 patients with gastrointestinal cancers who were cachexic in which a thalidomide-olanzapine-megasterol acetate combination attenuated the effects of cancer-anorexia-cachexia syndrome (Abstract #209); iv) a retrospective study on the role of adjuvant chemoradiation and chemotherapy in the treatment of advanced pancreatic cancer (Abstract #230); and v) the benefit of chemotherapy in patients with metastatic pancreatic cancer 80-year-old or more (Abstract #232). Based on the results presented at the meeting, we believe that the discussion of palliative care in the treatment of advanced pancreatic cancer must not conflate the notion of increased survival with increased quality of life, the latter of which is part and parcel of the goal of palliative care. We believe that future study on the effect on quality of life of early palliative-care interventions among people with pancreatic cancer is necessary. Image: Yale University School of Nursing. New Haven, CT, USA.